How workplace loneliness harms employee well-being: A moderated mediational model - Basit, Ameer A.; Nauman, Shazia (Frontiers in Psychology, 2023)
This study investigated the effect of workplace loneliness on work-related subjective well-being by proposing work engagement as an explanatory mechanism in the workplace loneliness—job dissatisfaction relationship. Moreover, the study examines the need to belong as a coping mechanism in the relationship between workplace loneliness and work engagement. Specifically, the study posits that workplace loneliness reduces the positive and fulfilling state of work engagement that in turn increases job dissatisfaction and that this mediation depends on the employee’s level of need to belong. Data were collected from employees (N = 274) working in diverse domestic and multinational organizations in Lahore, Pakistan. Results showed that workplace loneliness reduced the work engagement of lonely individuals that in turn increased their job dissatisfaction. However, the deleterious effect of workplace loneliness on work engagement was weaker for individuals having a higher need to belong. These findings have important implications for organizations wishing to mitigate the harmful effects of workplace loneliness on employees’ subjective well-being.